PENERAPAN MODEL ADDIE DAN SELF-DIRECTED LEARNING PADA PROGRAM ENGLISH STUDY AT HOME BERBASIS E-LEARNING DI EYE LEVEL CITRA GRAN CIBUBUR - Rawe, Tenri (Instruksional, 2022)
ABSTRACTThe emergence of the Covid-19 pandemic caused a change in the previously conventional learning process with face-to-face learning and then became online learning required by the government. This is motivated by efforts to increase effectiveness and flexibility in learning programs to keep them going in the pandemic era. One of the efforts is holding an English study at a home program based on e-learning. This article aims to apply the ADDIE model and self-directed learning to the e-learning-based English study at home program at Eye Level Citra Gran Cibubur. This R&D research chose the ADDIE model to be implemented, namely with five stages, Analysis, Design, Development, Implementation, and Evaluation. ABSTRAKMunculnya pandemi Covid-19 menimbulkan perubahan pada proses pembelajaran yang sebelumnya konvensional dengan pembelajaran tatap muka lalu menjadi pembelajaran online yang diwajibkan pemerintah. Dilatar belakangi oleh usaha untuk meningkatkan efektivitas dan fleksibilitas dalam menjalankan program pembelajaran agar tetap berlangsung di era pandemi. Salah satu upaya yaitu dengan mengadakan program English study at home berbasis e-learning. Tujuan dari penulisan artikel ini yaitu untuk penerapan model ADDIE dan self-directed learning pada program English study at home berbasis e-learning di Eye Level Citra Gran Cibubur. Penelitian R&D ini memilih model ADDIE untuk diimplementasikan yaitu dengan lima tahapan, Analysis (analisis), Design (rancangan/desain), Development (pengembangan), Implementation (implementasi/penerapan), dan Evaluation (evaluasi).